"How Sweet the Kill": Orgiastic Female Violence in Contemporary Re-visions of Euripides' The Bacchae - Hersh, Allison (Modern drama, 1992)
In her essay, "When We Dead Awaken: Writing as Re-Vision," Adrienne Rich defines "re-vision" as "the act of looking back, of seeing with fresh eyes, of entering an old text from a new critical direction." It is precisely the significance of the female author "entering an old text from a new critical direction" which seems central to the feminist re-visionary project, as the need to come to terms with "old texts" is a vital part of creating new ones. Indeed, confronting the extent to which textuality has historically been determined by patriarchal conventions clears a space for the representation of the diversity of female experience, enabling women to invoke the classical injunction to "know thyself," not through the distorting lens of male fantasies but rather through the lived experiences and the generative imagination of women authors. As Rich explains, "We need to know the writing of the past, and know it differently than we have ever known it; not to pass on a tradition but to break its hold over us." And perhaps nowhere is this attempt to "break [tradition's] hold" through the power of re-vision more salient, more intriguing or more chilling than in contemporary feminist re-visions of Euripides' The Bacchae.